EVALUATING THE VALUE OF TRADITIONAL VILLAGES: A CASE STUDY OF ABA TIBETAN AND QIANG AUTONOMOUS PREFECTURE, SICHUAN - zhou, zihua; Jamaludin, Omar; Doh, Shu Ing (Journal of Engineering and Technology (JET), 2026)
With the acceleration of industrialization and urbanization, the value of traditional villages has become increasingly marginalized, particularly in ethnic minority areas where cultural, ecological, and social structures face multiple challenges. This study focuses on the Aba Tibetan and Qiang Autonomous Prefecture in Sichuan Province, examining the preservation and development of traditional villages inhabited by Tibetan and Qiang ethnic groups. A multidimensional value assessment framework is constructed, encompassing four key dimensions: village environment, spatial pattern, traditional architecture, and intangible cultural heritage. By integrating literature analysis, field investigation, expert evaluation, and multi-source data, the study systematically identifies and classifies the comprehensive value of traditional villages in the region. The results reveal that these villages exhibit strong regional characteristics and cultural continuity in terms of environmental adaptation, construction techniques, cultural inheritance, and spatial organization, yet are currently threatened by spatial disruption, architectural degradation, cultural disconnection, and inadequate protection mechanisms. Based on the assessment, the villages are categorized into five types, and multi-level strategies are proposed, including planning-oriented protection, coordinated resource management, cultural revitalization, and digital empowerment. The study aims to explore sustainable development paths tailored to ethnic minority regions and provide theoretical and practical guidance for the scientific conservation and policy-making of traditional villages.